CYP4CS5-mediated thiamethoxam and clothianidin resistance is accompanied by fitness cost in the whitefly Bemisia tabaci. - Hu, J.; Fu, B.; Liang, J.; Zhang, R.; Wei, X.; Yang, J.; Tan, Q.; Xue, H.; Gong, P.; Liu, S.; Huang, M.; Du, T.; et al. (Pest Management Science, 2024)
Understanding the trade-offs between insecticide resistance and the associated fitness is of particular importance to sustainable pest control. One of the most devastating pest worldwide, the whitefly Bemisia tabaci, has developed resistance to various insecticides, especially the neonicotinoid group. Although neonicotinoid resistance often is conferred by P450s-mediated metabolic resistance, the relationship between such resistance and the associated fitness phenotype remains largely elusive. By gene cloning, quantitative reverse transcription (qRT)-PCR, RNA interference (RNAi), transgenic Drosophila melanogaster, metabolism capacity in vitro and 'two sex-age stage' life table study, this study aims to explore the molecular role of a P450 gene CYP4CS5 in neonicotinoid resistance and to investigate whether such resistance mechanism carries fitness costs in the whitefly. Our bioassay tests showed that a total of 13 field-collected populations of B. tabaci MED biotype displayed low-to-moderate resistance to thiamethoxam and clothianidin. Compared to the laboratory susceptible strain, we then found that an important P450 CYP4CS5 was remarkably upregulated in the field resistant populations. Such overexpression of CYP4CS5 had a good match with the resistance level among the whitefly samples. Further exposure to the two neonicotinoids resulted in an increase in CYP4CS5 expression. These results implicate that overexpression of CYP4CS5 is closely correlated with thiamethoxam and clothianidin resistance. RNAi knockdown of CYP4CS5 increased mortality of the resistant and susceptible populations after treatment with thiamethoxam and clothianidin in bioassay, but obtained an opposite result when using a transgenic line of D. melanogaster expressing CYP4CS5. Metabolic assays in vitro revealed that CYP4CS5 exhibited certain capacity of metabolizing thiamethoxam and clothianidin. These in vivo and in vitro assays indicate an essential role of CYP4CS5 in conferring thiamethoxam and clothianidin resistance in whitefly. Additionally, our life-table analysis demonstrate that the field resistant whitefly exhibited a prolonged development time, shortened longevity and reduced fecundity compared to the susceptible, suggesting an existing fitness cost as a result of the resistance. Collectively, in addition to the important role of CYP4CS5 in conferring thiamethoxam and clothianidin resistance, this resistance mechanism is associated with fitness costs in the whitefly. These findings not only contribute to the development of neonicotinoids resistance management strategies, but also provide a new target for sustainable whitefly control. © 2023 Society of Chemical Industry.